Elevated N-telopeptide as a potential diagnostic marker for bone metastasis in lung cancer: A meta-analysis - Liu, Boxuan (PLoS One, 2017)
BACKGROUND: Growing evidence indicates that the cross-linked N-telopeptide of type I collagen (NTx) is likely to be involved in the development of bone metastasis among lung cancer patients. We perform a meta-analysis to disclose the correlation between bone metastasis and NTx and also to evaluate its value in diagnosis of bone metastasis (BM) in lung cancer. METHOD: Electronic databases were searched and calculated the weighted mean difference (WMD) with 95% confidence interval (CI) to assess the expression difference of NTx between BM+ and BM- lung cancer patients. Moreover, we conducted a sensitivity and specificity test and drew a summary receiver operating characteristic curve (SROC) to assess the diagnostic value of NTx in discerning bone metastasis. RESULTS: A total of eleven studies with 1108 individuals were included in this analysis. The results showed an increased NTx was correlated with the incidence of lung cancer (P < 0.001). The overall sensitivity and specificity of serum NTx (sNTx) for discerning bone metastasis was 0.74 (95% CI = 0.67 to 0.79) and 0.85 (95% CI = 0.80 to 0.89), respectively. As for urine NTx (uNTx) the pooled sensitivity and specificity was 0.77(95% CI = 0.67 to 0.86) and 0.81(95% CI = 0.76 to 0.86). The area under the SROC curve was 0.8889(SE = 0.0255) and 0.8655(SE = 0.0254) for sNTx and uNTx respectively. CONCLUSIONS: The elevation of NTx in lung cancer was positively related with the development and progression of bone metastasis. A higher specificity over sensitivity of NTx suggested that it is a more accurate biomarker to distinguish patients without bone metastasis. Regarding SROC curve, sNTx may be a better choice.